Effect Of Green Human Resource Management Practices On Firm Environmental Innovativeness In The Malaysian Furniture Industry - Ali, Sufaid (2021)
The key objective of the study is to examine the relationship between key influential practices of green HRM such as green recruitment and selection, green training, green compensation, and green performance assessment, and firm environmental innovativeness among medium and large furniture manufacturing firms in Malaysia.